The relationship between country-of-origin image and brand image as drivers of purchase intentions - Diamantopoulos, Adamantios; Schlegelmilch, Bodo; Palihawadana, Dayananda (International marketing review, 2011)
Purpose - Against the background of mounting criticism of the country-of-origin (COO) construct, the purpose of this paper is to empirically contrast two competing perspectives of the potential influence of country-of origin image (COI) on purchase intentions.Design methodology approach - Based on personal interviews with over 300 UK consumers, the paper investigates the relative impact of COI and brand image as independent drivers ("orthogonality" perspective), and as causally-linked drivers ("irradiation" perspective) on consumers' intentions to buy specific US and Chinese brands.Findings - Controlling for the effects of brand familiarity, the analysis shows that COI impacts purchase intentions indirectly in that its influence is fully mediated by brand image. These findings are consistent with an "irradiation" perspective of COI effects and demonstrate that brand image evaluations already encapsulate consumers' COI perceptions.Research limitations implications - Based on the country brand combinations investigated, the results show that the recent criticism against the COO construct is largely unfounded and that the construct remains relevant to international marketing theory and practice.Practical implications - COO remains a relevant and powerful influence on brand perceptions and, through them, on buying intentions and needs to be carefully managed by companies.Originality value - The paper provides explicit empirical comparison of alternative models depicting potential COO influence on behavioural outcomes (brand image evaluations and purchase intentions) in distinct country brand combinations.